Hyperactivity Induced by Soluble Amyloid-β Oligomers in the Early Stages of Alzheimer's Disease - Hector, Audrey; Brouillette, Jonathan (Frontiers in Molecular Neuroscience, 2021)
Soluble amyloid-beta oligomers (Aβo) start to accumulate in the human brain one to two decades before any clinical symptoms of Alzheimer’s disease (AD) and are implicated in synapse loss, one of the best predictors of memory decline that characterize the illness. Cognitive impairment in AD was traditionally thought to result from a reduction in synaptic activity which ultimately induces neurodegeneration. More recent evidence indicates that in the early stages of AD synaptic failure is, at least partly, induced by neuronal hyperactivity rather than hypoactivity. Here, we review the growing body of evidence supporting the implication of soluble Aβo on the induction of neuronal hyperactivity in AD animal models, in vitro, and in humans. We then discuss the impact of Aβo-induced hyperactivity on memory performance, cell death, epileptiform activity, gamma oscillations, and slow wave activity. We provide an overview of the cellular and molecular mechanisms that are emerging to explain how Aβo induce neuronal hyperactivity. We conclude by providing an outlook on the impact of hyperactivity for the development of disease-modifying interventions at the onset of AD.